KONSEP PENERAPAN HUKUM KEWARISAN ISLAM NUSANTARA - Muhammad Patri Arifin (Fakultas Syariah Institut Agama Islam Negeri Palu, 2017)
Property is always become a medium to maintain relationships amonghuman beings, both when alive and after death. When a person is alive,his or her possessions can be used as media to maintain good relationswith others, as well as after death, abandoned property can still beused to maintain that relationship. One of them is through the divisionof inheritance.In Indonesia, although the provision of inheritance isstill largely in accordance with the general provisions that have beenformulated by the jurists, but for some people view the division ofjurists irrelevant to the situation and conditions of Indonesia, so thatsome inheritance inheritance formulas are reconstructed as what hasbeen formulated in Compilation of Islamic Law, there are evencompletely different due to the existing provisions.Hazairin, forexample, looks to be the case of a person who dies unlawfully, bothboy and girl. Hazarin distinguishes it in verses 12 and verse 176 surahan Nisa. In verse 12, you are not with a child, but with your father.Whereas in verse 176 the siblings are not with children and fathers. Sofor Hazairin there is no difference between siblings, having the samefather and mother. Therefore, many of you at least in the two verses,should be sought in other relationships. Likewise, the legalreconstruction offered by Munawir Syadzali and Muhammad Syahrurhas been widely considered in the formulation of his inheritance law inIndonesia, especially from academics and some judges in severalReligious Courts taking into consideration in every decision.